Development of a Novel Wearable Posture Correction Apparatus Using Advanced Accelerometry Techniques - Zhitomirsky, David (My University, 2010)
A novel posture correction apparatus was developed with the aim of stroke patient rehabilitation, specifically designed for patients with bodily neglect. The apparatus is based on an accelerometer system, capable of tracking tilt in three dimensions. The apparatus is portable and worn on the chest, and is extendable in design to other parts of the body. The approach to tilt sensing and posture correction taken here relies on small DC motor actuators implemented to notify the user of incorrect posture, based on their direction of tilt. The design takes into account patient differences, and has calibration procedures to accommodate for different users and prevent sensor drift. Tilt is also continuously monitored on a remote computer, where signals from the accelerometer are transmitted wirelessly via a microcontroller and RF module. It was found that the system could reliably track tilt and thus posture, and the feedback mechanism was effective at notifying the user about incorrect posture. Thus, this mountable system is an effective way to track and monitor posture, and is especially applicable to stroke patient rehabilitation.
Keywords: Biomedical; Electrical and Computer Engineering; Biomedical